Indistinguishability of Racket and Body Kinematics during Different Table Tennis Serves for International Elite and Intermediate Players - Yoichi Iino; Sho Tamaki; Yuki Inaba; Koshi Yamada; Kazuto Yoshida (Universidad de Granada, 2021)
Table tennis serves are strokes in which disguise and deception skills are important. This study aimed to investigate whether international elite table tennis players can make their racket and body kinematics more indistinguishable than intermediate players during three different serve types. Five former international elite and 8 intermediate players performed 3-12 trials of each serve type. The kinematics of the server's body and the racket was determined using a motion capture system. The time instant of racket-ball impact was determined using a high-speed video camera recorded at 2,000Hz, which was synchronized with the motion capture system. Misclassification rates when the serve type was classified using the racket and body kinematics were determined using linear discriminant analysis. Elite players showed higher misclassification rates for the racket kinematics than intermediate players during the early swing and follow-through phases. The body kinematics suggested that the elite players made their racket kinematics more indistinguishable using different approaches between the early swing and follow-through phases. The elite players tended to make the racket's angular velocity more similar and make the wrist rotational variables more indistinguishable in different serves compared to the intermediate players during the early swing phase. In contrast, the elite players made the racket's linear motion more variable within individual serve types than the intermediate players during the follow-through. The results suggest that intermediate players are recommended to practice making wrist angular motions more similar during the early swing phase and making racket linear motions more variable during the follow-through in order to improve the disguise skill in table tennis serves.